LANGUAGE ATTITUDE OF A BILINGUAL-BICULTURAL CHILD: CASE STUDY OF A MIXED-MARRIAGE FAMILY - SHOLIKHATUS SADIYAH, AYU (LANGUAGE HORIZON, 2018)
Abstract The researcher investigated the language attitude of the bilingual-bicultural child?s languages; Javanese language, Bahasa Indonesia and English. Qualitative method was the proper way to be applied in this study because the researcher purposed to do research in natural setting in order to get the natural data. To achieve the accurate, concrete and matched data, the researcher did interviews the informants (father, mother, child and budhe) and neighbors, did participant-observation and observed documents. The result presented the bilingual-bicultural child had positive attitude toward Javanese language, Bahasa Indonesia and English. It was cause by the influence of his parents and the surrounded people. They were open-minded family. They had high respect to all languages (in the world) without any judging which one was the minor language and which one was the major language. The child capable to differentiate what language to whom he communicated in order to appreciate his addressees and make them comfortable. Keywords: language attitude, bilingual, bicultural